Effects of agglomeration and pressing process on the properties of flat pressed WPC panels. Issue 6 (2nd March 2013) - Benthien, Jan T.; Thoemen, Heiko
Abstract This study discusses the influence of agglomeration process, press type and press parameters, on the physical and mechanical properties (water absorption (WA), thickness swelling (TS), internal bond strength, module of elasticity, and module of rupture) of flat pressed wood–plastic composite panels. Additionally, the effects of coupling agent and polymer's melt flow rate on panel properties are investigated. The compounding of the raw materials is done using a heating cooling mixer and a die ring agglomerator (DRA). Test panels are made using a laboratory scale single‐daylight press, an industrial single‐daylight press, and an industrial scale continuous double belt press (DBP). The best results were obtained using the DRA and the continuous DBP, with 24 h WA and TS values of below 1%, and a modulus of elasticity of more than 4500 N mm−2. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013